Agency and self-other asymmetries in perceived bias and shortcomings: Replications of the Bias Blind Spot and link to free will beliefs - Subramanya Prasad Chandrashekar; Siu Kit Yeung; Ka Chai Yau; Chung Yee Cheung; Tanay Kulbhushan Agarwal; Cho Yan Joan Wong; Tanishka Pillai; Thea Natasha Thirlwell; Wing Nam Leung; Colman Tse; Yan Tung Li; Bo Ley Cheng; et al. (Judgment and Decision Making, 2021)
Bias Blind Spot (BBS) is the phenomenon that people tend to perceive themselves as less susceptible to biases than others. In three pre-registered experiments (overall N = 969), we replicated two experiments of the first demonstration of the phenomenon by Pronin et al. (2002). We found support of the BBS hypotheses, with effects in line with findings in the original study: Participants rated themselves as less susceptible to biases than others (d = -1.00 [-1.33, -0.67]). Deviating from the original, we found an unexpected effect that participants rated themselves as having fewer shortcomings (d = -0.34 [-0.46, -0.23]), though there was support for the target's main premise that BBS was stronger for biases than for shortcomings (d = -0.43 [-0.56, -0.29]). Extending the replications, we found that beliefs in own free will were positively associated with BBS (r ~ 0.17–0.22) and that beliefs in both own and general free will were positively associated with self-other asymmetry related to personal shortcomings (r ~ 0.16–0.24). Materials, datasets, and code are available on https://osf.io/3df5s/.